Fatty Liver Disease: A Wake Up Call - Ahasan, HAM Nazmul; Bala, Chandra Shekhar; Biswas, Sarmistha; Minnat, Baharul; Hossain, Homayra Tahseen (Bangladesh Journal of Medicine, 2016)
Abstract not available Bangladesh J Medicine Jan 2016; 27(1) : 27-32